Public health evaluation and the social determinants of health - Kelley, Allyson, 1976- (Routledge studies in public health, 2020)
"Compelling evidence shows health disparities are the result of inequalities in income, education, limited access to medical care, substandard social environments, and poor economic conditions. This book introduces these social determinants of health, discusses how they relate to public health programs, and explains how to design and evaluate interventions bearing them in mind. Arguing that many public health programs fail to be as effective as they could be, because they ignore the underlying causes of health disparities, this important reference gives concrete examples of how evaluations focusing on the social determinants of health can alleviate health inequalities, as well as step-by-step guidance to undertaking them. This resource blends current research, existing data, and participatory evaluation methods. It is designed for teachers, students, practitioners and policymakers interested in public health programming and evaluation"--